Chloroplast Lipids Metabolism and Function. A Redox Perspective - Hernández, M. Luisa; Cejudo, Francisco Javier (Frontiers in Plant Science, 2021)
Plant productivity is determined by the conversion of solar energy into biomass through oxygenic photosynthesis, a process performed by protein-cofactor complexes including photosystems (PS) II and I, and ATP synthase. These complexes are embedded in chloroplast thylakoid membrane lipids, which thus function as structural support of the photosynthetic machinery and provide the lipid matrix to avoid free ion diffusion. The lipid and fatty acid composition of thylakoid membranes are unique in chloroplasts and cyanobacteria, which implies that these molecules are specifically required in oxygenic photosynthesis. Indeed, there is extensive evidence supporting a relevant function of glycerolipids in chloroplast biogenesis and photosynthetic efficiency in response to environmental stimuli, such as light and temperature. The rapid acclimation of higher plants to environmental changes is largely based on thiol-based redox regulation and the disulphide reductase activity thioredoxins (Trxs), which are reduced by ferredoxin (Fdx) via an Fdx-dependent Trx reductase (FTR). In addition, chloroplasts harbour an NADPH-dependent Trx reductase C (NTRC), which allows the use of NADPH to maintain the redox homeostasis of the organelle. Here, we summarize the current knowledge of chloroplast lipid metabolism and the function of these molecules as structural basis of the complex membrane network of the organelle. Furthermore, we discuss evidence supporting the relevant role of lipids in chloroplast biogenesis and photosynthetic performance in response to environmental cues in which the redox state of the organelle plays a relevant role.